2008
DOI: 10.1097/aud.0b013e3181775e03
|View full text |Cite
|
Sign up to set email alerts
|

Interaural Time Discrimination of Envelopes Carried on High-Frequency Tones as a Function of Level and Interaural Carrier Mismatch

Abstract: Objectives-The present study investigated interaural time discrimination for binaurally mismatched carrier frequencies in listeners with normal hearing. One goal of the investigation was to gain insights into binaural hearing in patients with bilateral cochlear implants, where the coding of interaural time differences may be limited by mismatches in the neural populations receiving stimulation on each side.Design-Temporal envelopes were manipulated to present low frequency timing cues to high frequency auditor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 45 publications
3
16
0
Order By: Relevance
“…In NH subjects, ITD thresholds as a function of mismatch have been measured using amplitude-modulated (AM) signals (Henning, 1974;Nuetzel and Hafter, 1981;Blanks et al, 2007;Blanks et al, 2008). The consistent trend in the results from these studies has been that with increasing mismatch, ITD JNDs increased.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…In NH subjects, ITD thresholds as a function of mismatch have been measured using amplitude-modulated (AM) signals (Henning, 1974;Nuetzel and Hafter, 1981;Blanks et al, 2007;Blanks et al, 2008). The consistent trend in the results from these studies has been that with increasing mismatch, ITD JNDs increased.…”
Section: Introductionmentioning
confidence: 76%
“…The reduced ability to perceive ITDs and ILDs as changes in the lateral position of a sound source may partially explain the increase in ITD and ILD discrimination thresholds observed in bilateral CI users when measured with a non-pitch-matched pair of electrodes (e.g., van Hoesel, 2004;Francart and Wouters, 2007;Blanks et al, 2008;Poon et al, 2009;Goupell et al, 2013b). Specifically, if the JND is a measure of the smallest perceptible change in the lateral position of an auditory image, then the smallest JND would be at the steepest part of the lateralization curve, which can be assumed to pass through an ITD or ILD of zero.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the very small peak level differences of the conditions with short off times the interpretation of the peak level effect is restricted to long off times. Previous studies on the effect of the stimulus level either co-varied the slope steepness (e.g., Dye and Hafter, 1984;Klein-Hennig et al, 2011;Blanks et al, 2008;Dreyer and Oxenham, 2008) or the modulation depth (e.g., Klein-Hennig et al). Klein-Hennig et al concluded that their peak-level effect was due to the co-variation of the slope steepness with the peak level.…”
Section: E Discussionmentioning
confidence: 99%
“…Matching the place of excitation in the cochleas is not strictly required for sensitivity to ITD in NH subjects [Blanks et al, 2008;Nuetzel and Hafter, 1981]. In bilateral CI listeners, the sensitivity to a mismatch in place of excitation is even smaller [Poon et al, 2009].…”
Section: Methodsmentioning
confidence: 99%